EFFECTIVENESS OF MOBILE ASSISTED LANGUAGE LEARNING (MALL) IN ENHANCING SPEAKING SKILL EFL STUDENTS’ AT SMP NEGERI 45 PALEMBANG - Septi Purnama Sari; Tahrun; Ana Theriana (Universitas PGRI Palembang, 2024)
The purpose of this study is to assess how well Mobile Assisted Language Learning (MALL) at SMPN 45 Palembang improves speaking abilities in English as a foreign language (EFL). Using a pre-experimental approach, the study involves a single group of students from the same class using the MALL method. This study is quantitative in nature and uses oral pre- and post-test data gathering methods in a single class of students at SMP Negeri 45 Palembang. With an average pre-test score of 61.69 and an average post-test score of 79.3, the statistical analysis and data gathering results demonstrate an improvement in English language proficiency following the implementation of MALL. These results demonstrate that MALL is a useful instrument for raising students' proficiency in speaking English as a foreign language (EFL).